The fallacy of constructing hybrid political orders: a reappraisal of the hybrid turn in peacebuilding. Issue 2 (14th March 2016) - Mac Ginty, Roger; Richmond, Oliver
ABSTRACT: This article reviews the recent academic and policy interest in hybridity and hybrid political orders in relation to peacebuilding. It is sceptical of the ability of international actors to manufacture with precision hybrid political orders, and argues that the shallow instrumentalization of hybridity is based on a misunderstanding of the concept. The article engages in conceptual-scoping in thinking through the emancipatory potential of hybridity. It differentiates between artificial and locally legitimate hybrid outcomes, and places the 'hybrid turn' in the literature in the context of the continued evolution of the liberal peace as it struggles to come to terms with crises of access and legitimacy.